PENTINGNYA PENDIDIKAN DALAM MENATA KEHIDUPAN SOSIAL KEMASYARAKATAN - Agus, Agus (MPP: Lembaga Penelitian Dan Studi Kebijakan, 2023)
Education is one of the main factors in changing a person's behavior or personality. However, education must also be in accordance with the Islamic perspective which is guided by the Al-Qur'an and Sunnah, because it is structured and directed in living this life. Surah al-'Alaq verses 1-5 is one of the many Powers of Allah that He sent down to the prophet Muhammad SAW. He was ordered to read even though he could not yet read, from these verses which contain many things about education, humans are able to answer all existing problems. This research method uses descriptive-qualitative research with an interdisciplinary approach. Many commentary books have studied this surah al-'Alaq, such as: Tafsir Ibn Katsir, Tafsir Al-Maraghi, Tafsir al-Misbah and others. Good education is able to change the existing social order in society in a more desirable direction